Rationalization of Bulgarian Rail Network - Arnautski, Georgi (Research Papers, 2005)
In study titled „Rationalization of Bulgarian rail network“ is addressed a problem of present interest, namely the restructuring of Bulgarian railway transport.Restructuring is an objective necessity, which comes from requirements of market economy and must change the former model of development of railway transport. However, restructuring retards because there are many problems that increase the price and the efforts for its implementation. With a view to all this it is needed to make a profound analysis of questions and problems, arising from restructuring and affecting the economic development of Bulgarian railway transport. Because of this the fundamental aim of the present study is to reveal an important restructuring element, which is rationalization of rail network.The present study is structured into introduction, three parts and conclusion, focused around specific problems. Consistently are examine the essence and directions of rail network’s rationalization, technical & economical indexes of main and branch railway lines, and some aspects of exploitation of these branch lines. At the end of study there are applications with parameters of all branch lines and these which were stopped from exploitation.With the purpose of clarify the process of futuring railway rationalization, the author is presenting a methodology, which government and railway’s leaders must follow, if they want to avoid impetuous decisions considering fortune of branch railway lines.Pending question of rationalization of Bulgarian railway network is not only topical, but historical, because liquidation of secondary branch lines will go about with unthinkable consequences for society and whole country.